Structure-Function Relationship of the Most Abundant Ceramide Subspecies Studied on Monolayer Models Using GIXD and Langmuir Isotherms - Brezesinski, Gerald; Opálka, Lukáš; Shen, Chen; Groetzsch, Carolin; Schneck, Emanuel; Eichner, Adina (Langmuir, 2025)
The main lipid compounds of the outermost layer of human skin are ceramides (CERs), free fatty acids, and cholesterol. Although numerous studies performed in the past could demonstrate the importance of these lipids for an intact skin barrier function, knowledge about the impact of each single component on the lamellar lipid films is still lacking. Especially, the CERs are a very heterogeneous group with high relevance for a proper barrier. It was found that the reason for the high stability of the lamellae is related to the lipid structure and function, with the type and extent of interactions between the head groups of the individual CER subspecies being particularly important. Elucidating these at the molecular level could help us to understand CER phase behavior in general. Using grazing incidence X-ray diffraction and measurements of Langmuir isotherms, the current work investigated the lateral packing of the monolayers of different subclasses of C18:0 CERs at air-water interfaces, including phytosphingosine, sphingosine, and dihydrosphingosine CERs, all with either α-hydroxy and nonhydroxy N-acylated fatty acyl. We were able to observe clear effects of the minimal differences in the polar headgroup structures of the sphingoid bases, with respect to the number and position of hydroxyl groups and double bonds, on the CER arrangement regarding the compressibility and structure of the films they formed, revealing that the hydroxyl group at the C4 of the phytosphingosine CERs leads not only to the formation of a hydrogen bond network but also to a stable suprastructure, which might be of high benefit for the barrier properties of intact skin.
Keywords: difrakce rentgenového záření; Humans; Ceramides; lidé; Structure-Activity Relationship; vztahy mezi strukturou a aktivitou; ceramidy; X-Ray Diffraction